Multiple low-temperature thermochronology constraints on exhumation of the Tatra Mountains: New implication for the complex evolution of the Western Carpathians in the Cenozoic - Anczkiewicz, A.; Danisik, Martin; Srodon, J. (American Geophysical Union, 2015)
The tectonothermal evolution of the highest mountain range in the Carpathian arc—the Tatra Mountains— is investigated by zircon and apatite fission track and zircon (U-Th)/He (ZHe) dating methods in order to unravel the disputed exhumation and geodynamic processes in the Western Carpathians. Our data in combination with geological evidences reveal a complex Cenozoic history, with four major tectonothermal events: (i) a very low grade metamorphism of the crystalline basement at temperatures >240°C due to tectonic burial during the Eo-Alpine collision in the Late Cretaceous (~80 Ma); (ii) exhumation and cooling of the basement to temperatures <130°C related to postorogenic collapse during Late Cretaceous-Paleocene times; (iii) Middle Eocene-Early Miocene reheating to >150°C after burial to 5–9 km depths by the Paleogene fore-arc basin; (iv) final exhumation of the segmented basement blocks during Oligocene-Miocene (32–11 Ma) owing to lateral extrusion of the North Pannonian plate and its collision with the European foreland. The spatial pattern of thermochronological data suggests asymmetric exhumation of the Tatra Mountains, beginning in the northwest at ~30–20 Ma with low cooling rates (~1–5°C/Ma) and propagating toward the major fault bounding the range in the south, where the youngest cooling ages (16–9 Ma) and fastest cooling rates (~10–20°C/Ma) are found. Our data prove that the Tatra Mountains shared Cenozoic evolution of other crystalline core mountains in the Western Carpathians. However, the Miocene ZHe ages suggest that the Tatra Mountains were buried to the greatest depths in the Paleogene-Early Miocene and experienced the greatest amount of Miocene exhumation.